Management of staghorn renal stones. (15th October 2018) - Diri, Akif; Diri, Banu
Abstract: Staghorn stones are large branching stones that fill part of all of the renal pelvis and renal calyces and they can be complete or partial depending on the level of occupancy of the collecting system. Although kidney stones are commoner in men, staghorn stones are less often reported in men compared to women and they are usually unilateral. Due to the significant morbidity and potential mortality attributed to staghorn stones, prompt assessment and treatment is mandatory. Conversely, conservative treatment has been shown to carry a mortality rate of 28% in 10-year period and 36% risk of developing significant renal impairment. Staghorn stones are, therefore, significant disease entity that should be managed aggressively and effectively. Generally, the gold standard treatment for staghorn stones is surgical with a view to achieve stone-free collecting system and preserve renal function. Percutaneous nephrolithotomy should be the recommended first-line treatment for staghorn stones. Other non-surgical options are usually considered in combination with surgery or as monotherapy only if patients are surgically unfit. The decision for optimal treatment of staghorn stones should be individualized according to the circumstances of the patient involved and in order to do so, a closer look at the advantages and disadvantages of each option is necessary.